Income Insurance Policy of Rice Farmers problems, obstacles and impacts, as well as propose guidelines for policy implementation - Sripai, Manit; Dokchan , Phasakorn (Journal of Modern Learning Development, 2022)
This article was written to study the implementation of the income insurance policy of rice farmers. Study the problems, obstacles and impacts in implementing the policy. to propose guidelines for implementing the policy of rice farmers in Mueang Phitsanulok District Phitsanulok Province The researcher expects that this vichai will bring benefits to Rice farmers earn higher and rice farmers suffer less. including reducing the inequality of Thai farmers In academics, it can be used as a form of policy. can be taken into account in the continuation of the policy spatial economics in the area of Mueang District Phitsanulok Province improved Get to know the problems, obstacles and impacts on rice farmers in the area can be used as a guideline for solving problems of rice farmers in the area